The NFKB1 Promoter Polymorphism (-94ins/delATTG) Is Associated with Susceptibility to Cytomegalovirus Infection after Kidney Transplantation and Should Have Implications on CMV Prophylaxis Regimens - Nowak, Hartmuth (Cells, 2021)
Infections with cytomegalovirus (CMV) are one of the most frequent opportunistic infections in kidney transplant recipients. Current risk-adapted CMV chemoprophylaxis regimens are based almost solely on the donor and recipient CMV serostatus. Of note, the NFKB1 -94ins/delATTG promoter polymorphism was recently associated with a higher risk of CMV infection. Since single genetic association studies suffer from poor reliability for drawing therapeutic implications, we performed this confirmatory study and included 256 kidney transplant recipients from 2007 to 2014 in this retrospective study. Patients were genotyped for the -94ins/delATTG NFKB1 promoter polymorphism and followed up for 12 months. The incidence of CMV infection within 12 months after kidney transplantation was 37.5% (33/88) for the ins/ins, 21.5% (28/130) for the ins/del, and 23.7% (9/38) for the del/del genotypes (p = 0.023). Moreover, we evaluated the time of CMV infection onset. Ins/ins carriers had primarily late-onset CMV infection (median 194 days; interquartile range (IQR) 117–267 days) compared with heterozygous (ins/del; median 158 days; IQR 82–195 days) and homozygous deletion allele carriers (del/del; median 95 days; 84–123 days). Multivariate-restricted Cox regression model confirmed the ins/ins genotype to be an independent risk factor for the development of late-onset CMV infections. These findings should have an impact on post-kidney transplantation CMV chemoprophylaxis regimens.